Evaluation of a Prototype of a Novel Galactomannan Sandwich Assay Using the VIDAS® Technology for the Diagnosis of Invasive Aspergillosis - Gallet, Salomé; Garnaud, Cécile; Dragonetti, Céline; Rivoiron, Sophie; Cognet, Odile; Guo, Yuping; Lesénéchal, Mylène; Maubon, Danièle; Cornet, Muriel (Frontiers in Cellular and Infection Microbiology, 2021)
Objectives To evaluate the analytical and clinical performance of a prototype of a VIDAS® Galactomannan (GM) unitary test (bioMérieux, Marcy l’Etoile, France) and compare to that of the PlateliaTM Aspergillus Ag assay (Bio-Rad, CA, USA). Methods Repeatability, reproducibility, and freeze-thaw stability of VIDAS®GM were evaluated. Sera from patients at risk of IA were concurrently tested with both the VIDAS®GM and PlateliaTM Aspergillus Ag assays. Correlations between the two assays were assessed by Passing Bablok (PB) regression and performance by ROC analysis. Results The correlations between the VIDAS®GM indexes after one and two cycles of freezing/thawing were r=1.00 and r=0.989, respectively. The coefficients of variation for negative, low-positive, and positive sera were 13%, 6%, and 5% for repeatability and 14.4%, 7.2%, and 5.5 % for reproducibility. Overall, 126 sera were tested with both assays (44 fresh and 82 frozen). The correlation between VIDAS®GM and PlateliaTM Aspergillus Ag was r=0.798. The areas under the curve of the ROC analyses were 0.892 and 0.894, for VIDAS®GM and PlateliaTM Aspergillus Ag, respectively. Conclusions This new VIDAS®GM prototype assay showed adequate analytical and clinical performance and a good correlation with that of PlateliaTM Aspergillus Ag with 126 sera, although these results need to be confirmed in a larger prospective and multicentric study. As for the other VIDAS® assays, VIDAS®GM is a single-sample automated test using a solid reagent strip and receptacle. It is easy to use and suitable for rapid on-demand test results.